RE-AIM in Clinical, Community, and Corporate Settings: Perspectives, Strategies, and Recommendations to Enhance Public Health Impact - Harden, Samantha M.; Smith, Matthew Lee; Ory, Marcia G.; Smith-Ray, Renae L.; Estabrooks, Paul A.; Glasgow, Russell E. (Frontiers in Public Health, 2018)
The RE-AIM Framework is a planning and evaluation model that has been used in a variety of settings to address various programmatic, environmental, and policy innovations for improving population health. In addition to the broad application and diverse use of the framework, there are lessons learned and recommendations for the future use of the framework across clinical, community, and corporate settings. The purposes of this article are to: (A) provide a brief overview of the RE-AIM Framework and its pragmatic use for planning and evaluation; (B) offer recommendations to facilitate the application of RE-AIM in clinical, community, and corporate settings; and (C) share perspectives and lessons learned about employing RE-AIM dimensions in the planning, implementation, and evaluation phases within these different settings. In this article, we demonstrate how the RE-AIM concepts and elements within each dimension can be applied by researchers and practitioners in diverse settings, among diverse populations and for diverse health topics.